Scaling up of sweetpotato vine multiplication technologies in Phalombe and Chikwawa districts in Malawi: A gender analysis - Mudege, Netsayi N.; Mwanga, Robert O.M.; Mdege, N.; Chevo, T.; Abidin, P.E. (Informa UK Limited, 2018)
This paper adopts a feminist approach to analyse how processes of scaling up of technologies to promote adoption can reinforce or reduce gender inequalities. It focuses on sweetpotato vine multiplication in Phalombe and Chikwawa districts in Malawi, and uses data from focus group discussions and individual interviews with men and women farmers and extension workers. Findings suggest that perception biases towards regarding the farmer as male results in women being overlooked in training, as well as the devaluation of women’s knowledge, which jeopardises their ability to adopt new sweetpotato technologies that are being scaled up/ rolled out. Technologies are often rolled out within institutional contexts where women are in positions subordinate to men, resulting in women not being able to fully and independently adopt them. Sweetpotato technology choices are also influenced by access to resources such as land, irrigation systems and labour. Women often lack these. Sweetpotato vine multiplication may increase women’s workload leading women to dis-adopt. The implications of this research are that scaling up strategies to promote technology adoption by women should go beyond the technology itself to restructuring both the technical and nontechnical aspects of agriculture so that women can fully benefit from improved technologies. From this perspective the physical and institutional context in which the technology is implemented has to be understood and any necessary adjustment made to ensure that both men and women adopt the technology and benefit from it.